Определение запятненности звезд солнечного типа со сверхмощными вспышками - Акопян, А. А.
This paper considers the problem of determining the degree of spottedness of solar-type stars with superflares. The main focus is on the application of a method previously developed by the author for estimating the spotiness of flaring stars based on the chronology of recorded flares. The method is based on determining the periodic function of flare frequency based on statistical analysis of time series of flares, interpreted as a Poisson process with a cyclic parameter related to the period of the star's axial rotation. Converting this function into a von Mises distribution density function allows us to move from the frequency of flares to estimating the angular distribution of stellar spots and determine the effective surface area covered by spots. Nine of the most active solar-type stars from the Okamoto et al. catalog were studied, for which the axial rotation periods were calculated based on the chronology of recorded flares, and the flare distribution concentration coefficients and angular distributions of spots were obtained. The estimated values of spot coverage range from 1-4% for the least spotted to 10% for the most spotted hemispheres, which significantly exceeds the values for the Sun. Comparison with the results of Okamoto et al. showed a high degree of agreement - the correlation coefficient r = 0.896. The developed approach demonstrates the possibility of determining the spotting of stars based on the time series of flare activity without the use of high-resolution photometric or spectroscopic data, which makes it a valuable tool for statistical studies of the magnetic activity of solar-type stars exhibiting super-powerful flares.
Keywords: Астрофизика